Metabonomic analysis of tumor microenvironments: a mini-review - Zeng, Zeng; Chen, Cong-Xian (Frontiers in Oncology, 2023)
Metabonomic analysis is the vital part of studying cancer progression. Metabonomic crosstalk such as nutrient availability, transformation in physicochemical way and intercellular interactions can affect tumor metabolism. Many original studies have demonstrated that metabolomic have importance in some aspects of tumor metabolism. In this mini-review, we sum up the definition of metabolomics and how metabolomics can help change tumor microenvironment especially on three metabonomic tumors’ pathways. Just like non-invasive biofluids are identified early biomarkers on the development of tumor, metabolomics can also predict the difference of tumor drugs response, drug resistance and efficacy. We conclude the importance of metabolomics in tumor metabolic and how it can affect oncology drugs in cancer therapy.